The Benefits of Using YouTube and Videos for Enhancing Students Speaking Skills in Secondary Level: A Review - Azza Nur Layla; Dyah Sekar Arum; Melani Mayasari; Agrissto Bintang Aji Pradana (Prosiding University Research Colloquium, 2022)
Students in secondary school must be able to communicate effectively. Good secondarylevel speaking skills might help children gain confidence if they are chosen by the teacher to speak English in public. As a result, it is critical to have media that can assist secondary pupils in enhancing their speaking abilities. Following the discovery of multiple studies in official journals, it is possible to infer that utilizing YouTube and videos as learning medium is useful for enhancing students' secondary level speaking skills.